PELAKSANAAN STANDAR PENGELOLAAN PENDIDIKAN DITINJAU DARI PERENCANAAN PROGRAM PADA SEKOLAH MENENGAH KEJURUAN KARTIKA I-1 PADANG - Adek Herlina Lubis (Universitas Negeri Padang, 2018)
This research aims to understand the implementing management of education standart which is reviewed by the side of the school program planning in SMK Kartika I-1 Padang. The kind of research is qualitative descriptive research that is using interviewing, observation, and dokumenting method as a method to collect data and the result of this study indicated that 1) the implementation of formulation standar and determination of school vision at SMK Kartika I-1 Padang has not fulfilled maximally that seen from the making of formulation and school vision. That is not through meeting of board of educator and lack of socialization to the shool stakeholder. 2) the implementation of formulation standard and arrangement of it mission also not fulfilled maximally that seen from the absence of board of educator. Meeting in formulation and arrangement of school mission and lack of socialization conducted by school. 3) implementation of formulation standar and determination of school objective has not fulfilled the criteria that seen from the absence board of educator meeting in making goals formulation and it has not been socialization conducted by school. 4) the implementation of formulation standard and arrangement of school work plan also not fulfilled maximally that seen from the absence of board of educator. Meeting in formulation and arrangement of school work plan and lack of socialization conducted by schoolKey words: Standard of School Management, School Program Planning